The Effect of Problem Based Learning to Critical Thinking Ability of M1 Students in Plant Biotechnology Materials - Iir Nur Choiriya; Erlia Narulita; Areerat Chuseng (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2019)
This study aimed to determine the effect of learning based on learning problems on students' critical thinking skills in plant biotechnology materials. This research is a quasi-experimental type using the design of